2020
DOI: 10.5194/hess-24-1939-2020
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impacts of human water use and climate variations on recent drying of Lake Urmia basin: the value of different sets of spaceborne and in situ data for calibrating a global hydrological model

Abstract: Abstract. During the last decades, the endorheic Lake Urmia basin in northwestern Iran has suffered from declining groundwater tables and a very strong recent reduction in the volume of Lake Urmia. For the case of Lake Urmia basin, this study explores the value of different locally and globally available observation data for adjusting a global hydrological model such that it can be used for distinguishing the impacts of human water use and climate variations. The WaterGAP Global Hydrology Model (WGHM) was for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…As a matter of fact, because of the drought in 2007 [Trigo et al, 2010] and the increase of groundwater extraction in this region, the mean groundwater level has been decreased considerably. Forootan et al [2014] have indicated that the groundwater storage in the Lake Urmia region changes by -11.2 mm/yr based on GRACE product from 2005 to 2011; see also Hosseini-Moghari et al [2020]. According to the findings of Tourian et al [2015], the lake's water level and its area has been decreased at an average rate of 34 ± 1 cm/yr and 220 ± 6 km 2 /yr between 2002 to 2014, respectively.…”
Section: Time Series Analysis Of Gnss Stationsmentioning
confidence: 93%
“…As a matter of fact, because of the drought in 2007 [Trigo et al, 2010] and the increase of groundwater extraction in this region, the mean groundwater level has been decreased considerably. Forootan et al [2014] have indicated that the groundwater storage in the Lake Urmia region changes by -11.2 mm/yr based on GRACE product from 2005 to 2011; see also Hosseini-Moghari et al [2020]. According to the findings of Tourian et al [2015], the lake's water level and its area has been decreased at an average rate of 34 ± 1 cm/yr and 220 ± 6 km 2 /yr between 2002 to 2014, respectively.…”
Section: Time Series Analysis Of Gnss Stationsmentioning
confidence: 93%
“…When saline lakes are connected to the underlying aquifer, groundwater abstractions for urban, industrial and/or agricultural uses may alter the hydroperiod of the waterbody by decreasing subsurface and surface runoff inputs. As a result, a disconnection of the lake from the aquifer and progressive desiccation can occur (Hosseini-Moghari et al, 2020).…”
Section: Environmental Impacts: Pollutionmentioning
confidence: 99%
“…S max is one of the key components for computing SMDAI. WaterGAP calibration and validation studies have 390 indicated that Smax may be underestimated in WaterGAP by a factor of two or more (Hosseini-Moghari et al, 2020). In order to understand the sensitivity of SMDAI to changes in S max , we ran a version of WaterGAP in which S max was doubled https://doi.org/10.5194/nhess-2020-265 Preprint.…”
Section: Sensitivity Of Smdai To the Smax Values Assumed In Watergapmentioning
confidence: 99%